2012
DOI: 10.1161/circheartfailure.112.968941
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Cardiac Myosin Binding Protein C Gene Transfer Rescues Myofilament Contractile Dysfunction in Cardiac Myosin Binding Protein C Null Mice

Abstract: Background Decreased expression of cardiac myosin binding protein C (cMyBPC) in the heart has been implicated as a consequence of mutations in cMyBPC that lead to abnormal contractile function at the myofilament level, thereby contributing to the development of hypertrophic cardiomyopathy in humans. It has not been established whether increasing the levels of cMyBPC in the intact heart can improve myofilament and in vivo contractile function and attenuate maladaptive remodeling processes because of reduced lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
51
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(58 citation statements)
references
References 39 publications
7
51
0
Order By: Relevance
“…Thus, the differential impact of Myk461 on k rel observed here is likely related to inherent differences in XB behavior between KO and WT myocardium. It is known that cMyBPC plays a dominant role in strain‐dependent XB detachment from actin and that XBs are destabilized in the absence of cMyBPC, thus resulting in faster rates of force decay 30, 37, 54. Perhaps Myk461 counters this effect by altering myosin head conformation in a manner that increases XB stability and/or slows XB turnover in KO myocardium, partly explaining the reduced force deficits induced by Myk461 in KO myocardium—a hypothesis that requires further validation using molecular studies specifically geared towards elucidating the contributions of cMyBPC on Myk461‐mediated modulation of XB behavior.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the differential impact of Myk461 on k rel observed here is likely related to inherent differences in XB behavior between KO and WT myocardium. It is known that cMyBPC plays a dominant role in strain‐dependent XB detachment from actin and that XBs are destabilized in the absence of cMyBPC, thus resulting in faster rates of force decay 30, 37, 54. Perhaps Myk461 counters this effect by altering myosin head conformation in a manner that increases XB stability and/or slows XB turnover in KO myocardium, partly explaining the reduced force deficits induced by Myk461 in KO myocardium—a hypothesis that requires further validation using molecular studies specifically geared towards elucidating the contributions of cMyBPC on Myk461‐mediated modulation of XB behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps Myk461 counters this effect by altering myosin head conformation in a manner that increases XB stability and/or slows XB turnover in KO myocardium, partly explaining the reduced force deficits induced by Myk461 in KO myocardium—a hypothesis that requires further validation using molecular studies specifically geared towards elucidating the contributions of cMyBPC on Myk461‐mediated modulation of XB behavior. Nevertheless, the Myk461‐induced slowing in k rel in the KO myocardium would be expected to reduce overall ATP turnover rate and tension cost as XB detachment was shown to correlate well with tension cost,56, 57 which may improve systolic function in vivo and reduce pathological hypertrophy and remodeling in models of hypertrophy induced by reductions in cMyBPC 30, 32. Notably, a slowed k rel and increased XB “ on ” time following Myk461 incubation may underlie our observation that Myk461‐induced force generation reductions were not as pronounced in the KO myocardium (Table 2; Figure 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been multiple groups that have also demonstrated that reversal of established sarcomeric cardiomyopathy in the adult animal was not successful (8,9,11). In contrast, one study used a viral strategy to express MYBPC3 protein in the adult MYBPC3-null heart and reported partial improvement in systolic function and a reduction in heart mass 21 days after viral injection (47). However, the mice in this study were injected with a MYBPC3-expressing viral vector at a range of ages spanning 8 to 26 weeks and were then analyzed together.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, another obvious target is myosin binding protein C, which is the most commonly mutated protein in hypertrophic cardiomyopathy. Because most mutations cause disease through haploinsufficiency, gene therapy would be expected to be most effective in such conditions [107][108][109] . In skeletal and cardiac muscle, the balance between contraction and relaxation is readily shifted by physiological mechanisms…”
Section: Future Directionsmentioning
confidence: 99%